Sensing of endogenous retroviruses-derived RNA by ZBP1 triggers PANoptosis in DNA damage and contributes to toxic side effects of chemotherapy - Fang Wang; Kaiying Li; Wensheng Wang; Hui Jiang; Jiangping He; Jin Cai; Wenqing Ren; Yaxing Zhao; Qianqian Song; Yuan He; Yanlei Ma; Xiaona Feng; et al. (Cell Death and Disease)
Abstract Excessive DNA damage triggers various types of programmed cell death (PCD), yet the regulatory mechanism of DNA damage-induced cell death is not fully understood. Here, we report that PANoptosis, a coordinated PCD pathway, including pyroptosis, apoptosis and necroptosis, is activated by DNA damage. The Z-DNA binding protein 1 (ZBP1) is the apical sensor of PANoptosis and essential for PANoptosome assembly in response to DNA damage. We find endogenous retroviruses (ERVs) are activated by DNA damage and act as ligands for ZBP1 to trigger PANoptosis. By using ZBP1 knock-out and knock-in mice disrupting ZBP1 nucleic acid-binding activity, we demonstrate that ZBP1-mediated PANoptosis contributes to the toxic effects of chemotherapeutic drugs, which is dependent on ZBP1 nucleic acid-binding activity. We found that ZBP1 expression is downregulated in tumor tissue. Furthermore, in colorectal cancer patients, dsRNA is induced by chemotherapy and sensed by ZBP1 in normal colonic tissues, suggesting ZBP1-mediated PANoptosis is activated by chemotherapy in normal tissues. Our findings indicate that ZBP1-mediated PANoptosis is activated by DNA damage and contributes to the toxic side effects of DNA-damage-based chemotherapy. These data suggest that ZBP1 could be a promising therapeutic target to alleviate chemotherapy-related side effects.